2006
DOI: 10.1080/10473289.2006.10464429
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Perfluorooctanoate in Ambient Air near the Fence Line of a Manufacturing Facility: Comparing Modeled and Monitored Values

Abstract: In order to improve our understanding of the nature, measurement and prediction of salts of perfluorooctanoic acid (PFOA) in air, two studies were performed along the fence line of a fluoropolymer manufacturing facility. First, a six-event, 24-hr monitoring series was performed around the fence line using the OSHA versatile sampler (OVS) system. Perfluorooctanoate concentrations were determined as perfluorooctanoic acid (PFOA) via liquid chromatography and mass spectrometry. Those data indicated that the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 23 publications
4
85
0
Order By: Relevance
“…Berger et al [168] observed PFSAs and PFCAs in the particulate phase of air samples collected in England, at concentrations ranging from nondetectable values (PFUA and PFDoA) to 828 pg/m 3 (PFOA). PFOA was observed at elevated concentrations of 0.1 to 3.84 mg/m 3 in ambient air outside a manufacturing facility [171]. A recent investigation of arctic glacial ice caps that receive contamination solely from the atmosphere also reported the observation of PFNA, PFOA, PFDA, PFUA and PFOS [113].…”
Section: Atmospherementioning
confidence: 93%
“…Berger et al [168] observed PFSAs and PFCAs in the particulate phase of air samples collected in England, at concentrations ranging from nondetectable values (PFUA and PFDoA) to 828 pg/m 3 (PFOA). PFOA was observed at elevated concentrations of 0.1 to 3.84 mg/m 3 in ambient air outside a manufacturing facility [171]. A recent investigation of arctic glacial ice caps that receive contamination solely from the atmosphere also reported the observation of PFNA, PFOA, PFDA, PFUA and PFOS [113].…”
Section: Atmospherementioning
confidence: 93%
“…34 The adjacent Xiaoling River also showed elevated levels of Σ 10 PFAAs (152 ng/L), and the similar composition profiles with a high contribution of PFBS (Figure 3) indicate that this river could be affected by the same fluorine chemical park as Daling River. Potential transport pathways could be atmospheric emissions of fluorinated surfactants from fluoropolymer manufacture 35 or wastewater through drainage channels connecting the rivers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Neutral volatile PFASs such as fluorotelomer alcohols (FTOHs) and perfluoroalkane sulfonamide substances are transported mainly in the gaseous phase and may degrade to less volatile perfluoroalkyl acids (PFAAs) including perfluoroalkyl carboxylic acids (PFCAs) and perfluoroalkane sulfonic acids (PFSAs) (Schenker et al 2008a, Young andMabury, 2010). These PFAAs can also be directly emitted to the atmosphere by manufacturing processes (Barton et al, 2006) where they are bound onto particles or dissolved in cloud, rain, or fog droplets (Arp and Goss, 2009).…”
Section: Introductionmentioning
confidence: 99%